Beyond the Four Varnas: The Untouchables in India - Prabhati Mukherjee; MUKHERJEE (Prabhati) (Delhi Motilal Banarsidass, 1988)
Who were the untouchables in India?and why and when did they become so? are some of the question the present study attempts to answer. As the sage proceeds, from the Rgveda onward, it unfold various facets of the problem faced by these people.
Keywords: India; Dalits; Civilization